Linguistic Disposition of Nazeer - Shafqat Zahoor; dr. rukhsana baloch (Zaban-o-Adab, 2021)
Contemporary critics of Nazir objected to Nazir’s language to be ignoble or a non-standard language, perhaps they had no idea that the same language of common folk would one day be a celebrated language. Nazeer’s language is not only a vernacular language but Nazeer has also used language which is exemplified by Jafar Zatli in Urdu poetry before and it is interesting to note that even these languages ??were not considered creditable. But the fact is, these are such two poets from whom a student of Urdu Linguistics can fully gratify his need in a true sense. In this article, Nazeer’s occupancy is surveyed as to what changes he made in the language.